Calmodulin-binding proteins that interact with actin filaments in a Ca2+-dependent flip-flop manner: survey in brain and secretory tissues. - Sobue, K (1983)
Regulatory actions of calmodulin on the contractile apparatus and cytoskeleton of smooth muscle and nonmuscle tissue are mediated by a number of specific calmodulin-binding proteins that bind to F-actin in a flip-flop manner--i.e., they bind to calmodulin or F-actin depending on the presence or absence, respectively, of Ca2+. A survey for such proteins in brain, adrenal gland, and pituitary gland identified six polypeptides on polyacrylamide gels--Mr 340,000 (band 1), Mr 240,000/235,000 doublet (band 2), Mr 150,000 (band 3), Mr 129,000 (band 4), Mr 105,000 (band 5), and Mr 94,000 (band 6)--as flip-flop-regulated calmodulin- and F-actin-binding polypeptides. In addition to these polypeptides, a Mr 58,000 non-flip-flop calmodulin-binding actin-binding polypeptide (band 7) was found in all tissues examined. Band 2 was identified as calspectin (spectrin-related protein; fodrin). The flip-flop regulation of calspectin required the presence of a heat-labile nondialyzable factor contained in a supernatant fraction of brain homogenates. Band 1 was distinct from microtubule-associated proteins (MAPs) 1 and 2. However, when band 1 polypeptide was kept on ice 3 days, it converted to a lower molecular weight doublet that migrated with MAP2 on NaDodSO4 gel electrophoresis. Bands 1 and 2 were found in all tissues examined.